Positive and negative temperature dependences of electron-impact ionization in In[sub 0.53]Ga[sub 0.47]As - Choo, K. Y.; Ong, D. S. (2005)
The electron-impact ionization coefficient (alpha) in In0.53Ga0.47As increases with temperature at electric fields below 200 kV/cm, in contrast to most crystalline semiconductors. It exhibits conventional negative temperature dependence at higher fields. A four-valley analytical band Monte Carlo model is used to study this anomalous behavior. The simulations show that both alloy scattering and the temperature dependence of the impact ionization threshold energy contribute to the temperature dependence of alpha. At low fields, we find that most ionization events occur in the first conduction band causing an increase of alpha with temperature in In0.53Ga0.47As. At high fields, alpha decreases with temperature again because of the reduced hot-electron population in the second conduction band. (c) 2005 American Institute of Physics.